Characterization of glioblastoma in an orthotopic mouse model with magnetic resonance elastography. (29th November 2017) - Schregel, Katharina; Nazari, Navid; Nowicki, Michal O.; Palotai, Miklos; Lawler, Sean E.; Sinkus, Ralph; Barbone, Paul E.; Patz, Samuel
Abstract : Glioblastoma (GBM) is the most common primary brain tumor. It is highly malignant and has a correspondingly poor prognosis. Diagnosis and monitoring are mainly accomplished with MRI, but remain challenging in some cases. Therefore, complementary methods for tumor detection and characterization would be beneficial. Using magnetic resonance elastography (MRE), we performed a longitudinal study of the biomechanical properties of intracranially implanted GBM in mice and compared the results to histopathology. The biomechanical parameters of viscoelastic modulus, shear wave speed and phase angle were significantly lower in tumors compared with healthy brain tissue and decreased over time with tumor progression. Moreover, some MRE parameters revealed sub‐regions at later tumor stages, which were not easily detectable on anatomical MRI images. Comparison with histopathology showed that softer tumor regions contained necrosis and patches of viable tumor cells. In contrast, areas of densely packed tumor cells and blood vessels identified with histology coincided with higher values of viscoelastic modulus and shear wave speed. Interestingly, the phase angle was independent from these anatomical variations. In summary, MRE depicted longitudinal and morphological changes in GBM and may prove valuable for tumor characterization in patients. Abstract : A longitudinal study of glioblastoma biomechanical properties in mice was performed using magnetic resonance elastography (MRE). The tumor was softer than healthy tissue and its stiffness progressively decreased with age. Different tumor sub‐regions were easily observed on both MRE and histology but not on T2w scans.